2021
DOI: 10.21203/rs.3.rs-244799/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neonatal Hypoxic-Ischemic Encephalopathy Diagnosis and Treatment: A National Survey in China

Abstract: Background: Neonatal hypoxic-ischemic encephalopathy (HIE) affects as many as 100,000 infants each year in China. Therapeutic hypothermia reduces HIE related mortality and long-term neurodevelopmental disabilities. National guidelines for HIE management were published a decade ago. This study aimed to investigate the current status of HIE diagnosis and treatment in China. Method: This prospective cross-sectional national survey used a questionnaire evaluating practices related to HIE management. Descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Neonatal HIE accounts for 15.2% of mortality under the age of five, in addition, the mortality rate of neonatal moderate or severe HIE is high, and the rate of severe neurological disability in survivors is up to 55%-73% [ 6 ]. Despite of significant improvements in neonatal care, HIE continues to exist in developed countries and a disproportionately high burden remains in low and middle income countries [ 7 11 ]. There are 15–18 million live births in China each year, and the incidence of neonatal HIE is estimated to be 3–6 per 1000 live births [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal HIE accounts for 15.2% of mortality under the age of five, in addition, the mortality rate of neonatal moderate or severe HIE is high, and the rate of severe neurological disability in survivors is up to 55%-73% [ 6 ]. Despite of significant improvements in neonatal care, HIE continues to exist in developed countries and a disproportionately high burden remains in low and middle income countries [ 7 11 ]. There are 15–18 million live births in China each year, and the incidence of neonatal HIE is estimated to be 3–6 per 1000 live births [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal HIE accounts for 15.2% of mortality under the age of ve, in addition, the mortality rate of neonatal moderate or severe HIE is high, and the rate of severe neurological disability in survivors is up to 55%-73% [6] . Despite of signi cant improvements in neonatal care, HIE continues to exist in developed countries and a disproportionately high burden remains in low and middle income countries [7][8][9][10][11] . There are 15-18 million live births in China each year, and the incidence of neonatal HIE is estimated to be 3-6 per 1000 live births [12] .…”
Section: Introductionmentioning
confidence: 99%
“…7, intrauterine distress, amniotic uid contamination are risk factors for moderate or severe HIE. Notably, we found no biological interaction between risk factors based on the additive model.…”
mentioning
confidence: 99%
“…To date, current strategies for clinical therapies involve anticonvulsants, hypothermia, electrolyte, and fluid management, as well as atropine and adrenaline applications. Nevertheless, there is still a lack of effective therapeutic approaches, primarily as a result of lacking mechanistic understanding of the pathophysiology of NHIE 7–9 . Therefore, the effective prevention and control measures in the study of the pathogenesis of NHIE should be urgently identified and developed 10–12 …”
Section: Introductionmentioning
confidence: 99%